Academic Supervision: Coaching to Improve the Performance of Islamic Religious Education Teachers at SMP Negeri 3 Selakau (International Journal of Education and Literature, 2024)
The purpose of this study is to describe and analyze: 1) Describe the implementation of academic supervision with coaching techniques carried out by the principal for Islamic Religious Education teachers; 2) Reveal the obstacles faced by the principal in implementing academic supervision with coaching techniques for Islamic Religious Education teachers; 3) Analyze the implications of implementing academic supervision with coaching techniques in improving the teaching performance of Islamic Religious Education teachers. This study uses a qualitative descriptive approach with a type of field research. Data collection uses three techniques, namely: observation, interview, and documentation techniques. Data analysis techniques start from data collection, data presentation and the process of drawing conclusions. The data validity checking techniques used are triangulation and member check. Research Results focus: 1) Implementation of academic supervision with coaching techniques has been carried out regularly and in stages, namely: a) Designed in a structured and sustainable manner, b) The principal prepares assessment instruments, scoring guidelines, supervision schedules, and socialization to teachers, c) Academic supervision includes planning, implementation and evaluation activities, d) academic supervision with coaching techniques through pre-observation activities, observation actions and post-observation; 2) Constraints in implementing academic supervision with coaching techniques: a) Limited time for the principal to carry out academic supervision optimally, b) Lack of initial understanding of teachers regarding the concept of coaching in academic supervision, c) teacher commitment to their responsibility to carry out actions that have been agreed upon between the coach and coachee; 3) Implications of supervision with coaching techniques on teacher performance: a) coaching not only provides feedback, but also builds a deeper relationship between the principal and teachers, b) coaching helps teachers reflect on and change their teaching practices to be more effective, c) academic supervision with coaching techniques is an effective supervision to encourage professionalism in improving teacher performance.